PENGARUH TEKNIK PERNAFASAN BUTEYKO TERHADAP FREKUENSI KEKAMBUHAN ASMA PADA PENDERITA ASMA BRONKHIAL DI UPT PUSKESMAS WILAYAH KERJA LIMA KAUM 1 KABUPATEN TANAH DATAR TAHUN 2017 - Yasherly Bachri (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
Asthma disease if not done prevention will result in relapse in asthma patients or recurrentasthma attacks. Asthma attacks that often recur to limit the activity of the patient evenfatal. Therefore, patients need to undergo therapy to overcome them. One method toimprove the way of breathing in asthmatics is the technique of breathing buteyko. Thepurpose of this research was to know the influenced the techniques of buteyko breathtoward frequencies of patients’ relapse asthma bronchial in UPT Puskesmas work districtLima Kaum 1 Kabupaten Tanah Datar 2017 Year. The design of this research was preeksperimen by one group pretest –postest design approach. Sampling technique in thisstudy using purposive sampling with a total sample of 12 people. The results of statisticaltests showed that there was a difference in the frequency of recurrence of bronchial asthmabefore and after given buteyko respiratory technique in bronchial asthma patients. Theimplications of research results of asthma patients can perform buteyko breathingtechniques to reduce the recurrence of asthma